Analysis of environmental microplastics by vibrational microspectroscopy: FTIR, Raman or both? - Kaeppler, Andrea; Fischer, Dieter; Oberbeckmann, Sonja; Schernewski, Gerald; Labrenz, Matthias; Eichhorn, Klaus-Jochen; Voit, Brigitte (Analytical and Bioanalytical Chemistry, 2016)
The contamination of aquatic ecosystems with microplastics has recently been reported through many studies, and negative impacts on the aquatic biota have been described. For the chemical identification of microplastics, mainly Fourier transform infrared (FTIR) and Raman spectroscopy are used. But up to now, a critical comparison and validation of both spectroscopic methods with respect to microplastics analysis is missing. To close this knowledge gap, we investigated environmental samples by both Raman and FTIR spectroscopy. Firstly, particles and fibres >500 μm extracted from beach sediment samples were analysed by Raman and FTIR microspectroscopic single measurements. Our results illustrate that both methods are in principle suitable to identify microplastics from the environment. However, in some cases, especially for coloured particles, a combination of both spectroscopic methods is necessary for a complete and reliable characterisation of the chemical composition. Secondly, a marine sample containing particles <400 μm was investigated by Raman imaging and FTIR transmission imaging. The results were compared regarding number, size and type of detectable microplastics as well as spectra quality, measurement time and handling. We show that FTIR imaging leads to significant underestimation (about 35 %) of microplastics compared to Raman imaging, especially in the size range <20 μm. However, the measurement time of Raman imaging is considerably higher compared to FTIR imaging. In summary, we propose a further size division within the smaller microplastics fraction into 500–50 μm (rapid and reliable analysis by FTIR imaging) and into 50–1 μm (detailed and more time-consuming analysis by Raman imaging). [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2023-03-20
Keywords: Environmental; FTIR spectroscopy; Microplastics; Raman spectroscopy